شكر المنة في نصر السنة - المكني, احمد بن محمد (1700)
Polemics against the Ibādīyah by a muftī of Tripoli, comprising an introduction, four chapters (bāb), and a conclusion. The end of the latter is missing.
Keywords: Manuscrits – Princeton; Polémique